The role of religious elements in digital well-being for Muslims - Asar, A. K.; Aziman, Abdullah (Springer, 2023)
There are diverse opinions among scientists nowadays regarding digital individuals’ well-being. Some focus on the role of spiritual elements, while others emphasise ethical elements. The main aim of this review is to highlight the importance of religious elements in digital well-being for human beings, particularly Muslims. Religions enforce moral behaviours by infusing a ‘god-fearing’ element into the believers. Even though there are various factors contributing to the digital well-being of mankind, religions have proven to have a more positive impact and effectiveness given their connection to supernatural agents. Moreover, for Muslims, religion constitutes the worldview of their existence and their daily life activities in this world. Those religious elements pave the right way for believers in dealing with technology, the internet, and technological devices. This article also proposed a brief theoretical framework of those Islāmic elements which play an important role in digital well-being for Muslims.